2014
DOI: 10.1371/journal.pone.0105535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Darwin’s Naturalization Hypothesis in Experimental Plant Assemblages: Phylogenetic Relationships Do Not Determine Colonization Success

Abstract: Darwin’s naturalization hypothesis (DNH) proposes that colonization is less likely when the colonizing species is related to members of the invaded community, because evolutionary closeness intensifies competition among species that share similar resources. Studies that have evaluated DNH from correlational evidence have yielded controversial results with respect to its occurrence and generality. In the present study we carried out a set of manipulative experiments in which we controlled the phylogenetic relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…In contrast, most studies exploring the effects of phylogenetic relatedness between invasives and natives on community resistance (i.e. phylogenetic species‐based indices) have yielded mixed (Jones et al , Liu et al , Poe , Lososová et al , Marx et al ) or non‐significant results (Castro et al , Fleming et al ). Nevertheless, a recent study by Tan et al () in a manipulative experiment with bacterial assemblages found evidence that phylogenetic relatedness to invaders was a better predictor of biotic resistance than the phylogenetic diversity of the community.…”
Section: ) Which Communities Are More Resistant To Invasion?mentioning
confidence: 99%
“…In contrast, most studies exploring the effects of phylogenetic relatedness between invasives and natives on community resistance (i.e. phylogenetic species‐based indices) have yielded mixed (Jones et al , Liu et al , Poe , Lososová et al , Marx et al ) or non‐significant results (Castro et al , Fleming et al ). Nevertheless, a recent study by Tan et al () in a manipulative experiment with bacterial assemblages found evidence that phylogenetic relatedness to invaders was a better predictor of biotic resistance than the phylogenetic diversity of the community.…”
Section: ) Which Communities Are More Resistant To Invasion?mentioning
confidence: 99%
“…; Castro et al . ) or how often plants will show a phylogenetic signal for mycorrhizal fungi (Montesinos‐Navarro et al . ).…”
Section: Mechanisms Of Mutualism Disruptionmentioning
confidence: 99%
“…To assess 'Darwin's Naturalization Conundrum' (DNC, Diez et al, 2008), the use of phylogenies is becoming standard (e.g. Strauss et al, 2006b;Cadotte et al, 2009bCadotte et al, , 2010Davies et al, 2010;Schaefer et al, 2011;Carboni et al, 2012;Bezeng et al, 2013;Park & Potter, 2013;Castro et al, 2014;Lim et al, 2014;Ordonez, 2014;Li et al, 2015;Lososov a et al, 2015). The inclusion of evolutionary information using a phylogenetic approach provides an accurate quantification of relatedness by comparing phylogenetic distances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of evolutionary information using a phylogenetic approach provides an accurate quantification of relatedness by comparing phylogenetic distances (i.e. difference in branch lengths) between native and invasive species (Proches ß et al, 2008;Cadotte et al, 2009b;Thuiller et al, 2010), and relatedness has been shown experimentally to be a useful predictor of invasion success (Jiang et al, 2010;(Cadotte & Strauss, 2011), but see Castro et al, 2014). In addition, because related species are more likely to share ecologically relevant functional traits (Webb et al, 2002), phylogenetic distance as measured on a molecular phylogeny of the species within a community is often viewed as a proxy for ecological similarity (Cadotte et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%